- PENEGAKAN HUKUM BAGI APARATUR SIPIL NEGARA YANG MEMAKAI NARKOTIKA BERDASARKAN UNDANG-UNDANG NO. 5 TAHUN 2014 : - - Muhammad Akrom Fahmi; Wiratno (Reformasi Hukum Trisakti, 2024)
The government committed to fighting drug abuse. Illicit trafficking and illicit or fraudulent drug consumption are not new in Indonesia. ASN has seen increase in cases of misappropriation or cheating of drug consumption lately. The problem in this research is how law enforcement can be applied to state Civil servants who carry out drug crimes and how is the process of dismissal of the state civil apparatus that stated to be credibly carrying out narcotics crimes based on personnel regulations stipulated by Act No. 5 of 2014 which discusses the State Civil apparatus and personnel regulations. This type of research is juridical normative, and nature descriptive, with conclusions made using deductive logic. The results showed that ASN, as prosecutor, could be sentenced to severe discipline in the direction of PP No. 53 of 2010 and dismissed not respectfully from his position by Act No. 5 of 2014. In the event of dismissal of an ASN that is not with due respect, the prosecutor can be proposed by the Deputy Attorney General supervision to the attorney general, and then, in the direction of PP No.20 of 2008, the attorney general determined and ruled the dismissal decision was not respectful.